Lussazioni pure di caviglia - Nobile, F.; Scipio, D.; Mangiavacchi, M.; Russo, L.; Sampieri, L.; Ciampalini, L. (Lo Scalpello - Journal, 2018)
PURE ANKLE DISLOCATIONPure ankle dislocation is a rare event in Orthopaedic and Traumatology Emergency Departments. As it constitutes anemergency, prompt reduction is mandatory to reduce the risk of neurovascular impairment. In most cases, high energytrauma (motor vehicle or sports accident) is the cause of pure tibiotalar dislocation, as it leads to forced plantarflexionand inversion or eversion of the foot; young men are more often involved and predisposing anatomical factors as wellas ligamentous laxity could favour dislocation. The following article provides a critical review of the current literaturein order to outline the epidemiology, treatment, outcome and possible complications of pure ankle dislocation.